Evaluating the Elklan Talking Matters Programme: Exploring the impact of a training programme for early years professionals on pre-school children's language development. (June 2020) - Clegg, Judy; Rohde, Carla; McLachlan, Henrietta; Elks, Liz; Hall, Alex
Training early years practitioners to facilitate the language development of young children is a widely used intervention. Evidence to support the effectiveness of training in terms of the impact of children's language development is limited. The Elklan Talking Matters programme is an accredited training programme for early years practitioners. Practitioners train to be Lead Communication Practitioners (LCPs) who cascade training across early years settings or Key Communication Practitioners (KCPs) who are embedded into these settings. The aim of this study was to identify if the Talking Matters Programme is effective in facilitating the language development of pre-school children. One hundred and twenty-six children from 13 early years settings were recruited (mean age 27.81 months; SD 4.90). Thirteen settings participated in the Talking Matters Programme (five LCP+KCP settings, four LCP settings and four control settings). At time 1, prior to practitioners participating in the programme, children completed the Pre-School Language Scales 5th Edition (PLS-5), a standardized assessment of receptive and expressive language. At time 1, 126 children completed the baseline assessment ( n = 43 in the LCP+KCP settings, n = 43 in the LCP settings and n = 40 in the control settings). Children then completed the post intervention (time 2) assessment approximately six months later. Children in the intervention groups (LCP+KCP settings and LCP settings) made more progress in their language development from time 1 to time 2 compared to the control. The children in the LCP+KCP settings made more gains than the children in the LCP settings. A significant main effect of groups and time was found but not an interaction of group scores with time, meaning the increases in scores were not statistically significant between the intervention and control groups. The study provides tentative evidence that the Talking Matters programme has a positive impact on pre-school children's language development.